Efficacy and safety of S-1 based adjuvant chemoradiotherapy for resected pancreatic ductal adenocarcinoma with high-risk pathological feature: a prospective, single-arm, interventional study. Issue 1 (15th March 2022) - Wu, Lili; Xu, Yaolin; Zeng, Zhaochong; Chen, Yixing; Zhou, Yuhong; Wang, Dansong; Sun, Jing; Lv, Minzhi; Du, Shisuo; Lou, Wenhui
Abstract: Objective: It remains unclear whether adjuvant chemoradiotherapy (CRT) improves survival outcome of pancreatic ductal adenocarcinoma (PDAC) patients after surgery. This study aimed to investigate the efficacy and safety of tegafur/gimeracil/oteracil (S-1)-based adjuvant concurrent chemoradiotherapy in resected PDAC patients with defined high-risk pathological features. Methods: We conducted a single-arm, prospective, and interventional study at Zhongshan Hospital Fudan University from December 2012 to December 2019 and the last follow-up was conducted in December 2021. This study was approved by the Ethics Committee of Zhongshan Hospital Fudan University on December 27, 2012 (approval No. B2012-139). Resected PDAC patients with high-risk pathological features, including positive resection margin, pathological T3-4N1-2M0 disease, peripancreatic fat invasion, microvascular invasion, and perineural invasion, were recruited. Primary endpoint was overall survival and secondary endpoints were disease-free survival, treatment toxicity, and 2-, 5-year survival rates. Results: A total of 54 patients were recruited. Mean age was 63.6 years old (±7.2). The distribution of T and N stages were 24.1% for T1, 46.3% for T2, 27.8% for T3, 1.9% for T4, 33.3% for N1, and 11.1% for N2. Seven patients had R1 resection. The median overall survival and disease-free survival were 27.1 and 13.7 months, respectively, while no fatal adverse events were recorded. Subgroup analyses showed differences in survival outcomes among patients with microvascular invasion, different N stages, and preoperative CA 19-9 levels. Further, a Cox proportional hazard model demonstrated associations of lymph node metastases, CA 19-9 level, and microvascular invasion with overall survival and disease-free survival. Conclusion: S-1-based adjuvant CRT showed promising efficacy and manageable toxicity in resected PDAC patients with high-risk pathological features.